BRANDING OF HIPMI PEDULI JAWA TENGAH THROUGH STRATEGIC COMMUNICATION ACTIVITIES AS COMMUNICATION MANAGER - Qorina, Devi Yuhanita; Setyabudi, Djoko; Naryoso, Agus; Rakhmad, Wiwid Noor (Interaksi Online, 2016)
The final task in the form of field work is based by HIPMI Peduli Jawa Tengah as a charity organization under the auspices of the Himpunan Pengusaha Muda Indonesia Regional Jawa Tengah (HIPMI Jawa Tengah) that recently established. The establishment of HIPMI Peduli Jawa Tengah aims to cultivate the spirit of social awareness and participation of entrepreneurs and societies in order to improve the social welfare of the Indonesian people on the social issues that happening nowadays. As a charities organization under the auspices of HIPMI Jawa Tengah, awareness of HIPMI Peduli Jawa Tengah is not widely known even by members of the HIPMI Jawa Tengah.The lack of awareness by HIPMI Peduli Jawa Tengah makes the participation of entrepreneurs and societies are less in any social activities undertaken by HIPMI Peduli Jawa Tengah. This leads to the small number of donors who participated through HIPMI Peduli Jawa Tengah that has not give maximum support at each social activities undertaken. Based on the concept of branding and persuasion theory, field work aims to increase awareness HIPMI Peduli Jawa Tengah and encourage the target audience to join and participate in any social activities undertaken by HIPMI Peduli Jawa Tengah.The implementation was held in August to September 2015 that makes it a total of 5 weeks, through a series of activities with the theme of education 1000 Book 1000 Goodness For Coastal Children, managed to get an increase in awareness activities HIPMI Peduli Jawa Tengah significantly from 25.84% to 84% and the increase of donation participation from 11.2% to 34%. Managed to get media partner, 5 social media accounts of Semarang City, 1 exclusive radio, and 1 exclusive print media. Managed to get positive publicity in 1 print media and 3 online media. This field work indicates that the "Branding HIPMI Peduli Jawa Tengah Through Strategic Communication Activity" was carried out according to goals specified by division communication manager.